Establishment Of An Agrobacterium-Mediated Transformation System And In Vitro Regeneration Protocol For Rice (Oryza Sativa Sp. Indica Var.) Mr219 - Chin, Wai Hoe (2008)

(untitled)
This study consisted of several parts which include development of tissue culture and regeneration system for local indica rice MR 219 variety, establishment of Agrobacterium-mediated transformation system and molecular analysis to confirm introduction of oil palm leaf-specific promoter in putative rice transformants Different concentrations of 2-4,D (0, 1.5, 3.0, 4.5, 7.5 and 10mg/l) were tested for embryogenic and nodular calli induction from scutellum region of indica rice using MS medium supplemented with 500 mg/L proline, 500 mg/L casein hydrolysate, 30 g/L sucrose and 2.5 g/L gelrite and it was shown that 3.0mg/l 2-4,D was the best concentration to use.Different concentrations of 6-benzylaminopurine (BAP) (1.0, 2.0, 4.0, 6.0 mg/l) alone or in combination with 0.5mg/l naphthalene acetic acid (NAA) and two different concentrations of Kinetin (1.0 and 2.0 mg/l) in MS media in the presence of 500 mg/L proline, 500 mg/L casein hydrolysate, 30 g/L sucrose and 6.0 g/L gelrite were used to determine the most suitable plant growth regulators for regeneration of rice plants. The results showed that BAP 6.0 mg/l alone is the best condition for multiple shoot formation from desiccated rice calli. Plasmid pCAMBIA 1301 is a binary vector having hygromycin resistant gene (hpt) as selectable marker gene in the T-DNA region. The minimal inhibitory concentration of hygromycin was determined by testing different concentrations of hygromycin ( 10, 20, 30, 50, 70 ,90mg/l) for survival of rice embryogenic callus. Hygromycin at 50 mg/l which gave 53.34% retarded growth of calli but with minimal browning was chosen as the most suitable for selection of putative transformants. This experiment together with the other tissue culture experiments were conducted and arranged in a Completely Randomized Design (CRD). The oil palm leaf-specific gene promoter was cloned individually into binary vector pCambia 1301 carrying β-glucuronidase (GUS) reporter gene after removal of the CaMV 35S promoter and the recombinant plasmids produced were transferred into Agrobacterium tumefaciens strain EHA105 and C58.Agrobacterium tumefaciens strain EHA 105 and C58 shown to contain oil palm leaf-specific promoter based on PCR analysis were used to transform rice calli. Calli subjected to heat and centrifugation treatments were found to be suscessfuly transformed based on GUS histochemical analysis. Different concentrations of antibiotics on the MS medium including carbenicilin (250, 500, 800, 1000, 1500, 1800 and 2000 mg/l), cefotaxime (250, 500, 800 mg/l), timentin (200,300 mg/l) either alone or in combination were not successful in eliminating Agrobacterium after transformation. PPM (plant preservative mixture) was found to be the best chemical to remove excessive Agroabcterium. Calli were subsequently transferred to regeneration medium (MS salts gelled with 500 mg/L proline, 500 mg/L casein hydrolysate, 30 g/L sucrose and 6 g/L gelrite, 50mg/l hygromycin B, pH 5.8) after hygromycin selection. Successful introduction of the oil palm tissue-specific promoters in putative transformants were confirmed via PCR and real time PCR analysis using primers designed based on the oil palm leaf-specific promoter sequence. Real time PCR analysis showed that the gene copy numbers of transgenic calli were not more than 2 copies per genome. Using GUS histochemical assay it was shown that CAMV 35S promoter but not the oil palm leaf-specific promoter can drive GUS expression in transformed rice calli.